A scoping review of social work evidence: defining the effectiveness of intervention / Asiyah Kassim - Kassim, Asiyah (2021)
There is growing attention on the need for all health and care professionals to be able to exhibit the effectiveness of their work. The need to understand what works in current social work practice is vital to understand the effectiveness of social work models of intervention and develop an evidence base that helps raise the quality of social work. This is depicted in the call for social work training and education to produce three main outcomes, namely the social worker as professional, the social worker as a practitioner, and the social worker as a social scientist that can understand and apply to their social work practice, the relevant principles, methods, and knowledge of social work as well as seeking to expand the understanding of social work through research and accumulating evidence (Croisdale-Appleby, 2019). However, many policymakers and practitioners find it difficult to access good-quality evidence on the effectiveness of social work interventions (Romeo, 2020). Research into social work practice is an evolving field hence, the need to investigate this concern is timely. This review thus aims to provide policymakers and practitioners an overview of the evidence on the effectiveness of social work with adults by assembling existing published research and identifying the existence of gaps by specifically answering this question: ‘What do we know about the effectiveness of social work with adults and how has it been measured?’. Social work with adults involves several different roles and functions, ranging from assessing, reviewing, and providing help to an individual, family, or career with complex family or social care needs, supporting people with complex or life-limiting health conditions, and safeguarding people at risk of abuse and neglect (The College of Social Work, 2018). This review does not concentrate on any single aspect of these but instead takes a broad-brush approach. This is a vital preliminary task in identifying the direction of any future work investigating specific areas of practice. The premise for ‘social work with adults’ was broad as it includes social work with different types of service users such as adults with a learning disability, mental health problem, or specific disability. From a wider perspective, the review seeks to identify broad topic areas where published empirical research was available and those where evidence was emerging, or which were under-researched.